Home Bias and the Power of Branding. Issue 1 (2nd January 2021) - Riff, Sivan; Yagil, Yossi
Abstract: The tendency to overinvest in local assets, which is called "home bias, " has been an enigma fascinating economists for many years. This study challenges the effect of home bias and suggests that the high global branding of companies might have an equal or even stronger influence compared with the influence of location. Using experimental methodology, the authors examine the effects of branding and location on the willingness of investors to invest in a certain asset. First, the results show that people prefer to invest in local compared with foreign assets. Second, the authors find that the effect of location is stronger within low-branded companies, while in high-branded companies, the effect of location is not significant. Third, the results show that people prefer to invest in high-branded companies than in low-branded companies and that the effect of branding is stronger within foreign companies, while the effect of branding is weaker within local companies. Last, the effect of branding is as strong as the effect of location.